Effects of low molecular weight peptides from monkfish (Lophius litulon) roe on immune response in immunosuppressed mice - Ren, Zhexin; Yang, Fei; Yao, Sijia; Bi, Lijun; Jiang, Guanqin; Huang, Ju; Tang, Yunping (Frontiers in Nutrition, 2022)
In this study, the immunomodulatory activation of low-molecular-weight peptides from monkfish (Lophius litulon) roe (named MRP) on cyclophosphamide (CTX)-induced immunosuppressed mice was investigated. Our results indicated that MRP (100 mg/kg/d BW) could significantly increase the mice’s body weight and immune organ index, improving the morphological changes in the spleen and thymus, enhancing the serum levels of interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, immunoglobulin (Ig) A, IgM, and IgG. Furthermore, MRP could improve CTX-induced oxidative stress, and activate the NF-κB and MAPK pathways in the spleen tissues. Our study indicated that MRP has good immunomodulatory activation toward immunosuppressed mice, and it shows potential to be developed as an immune adjuvant or functional food.